ANCAMAN KELESTARIAN JENIS SANTIGI (Phempis acidula) DI KAWASAN MANGROVE CAGAR ALAM MAUBESI KABUPATEN MALAKA NUSA TENGGARA TIMUR - Luisa M Manek; Yofris Puay (Politeknik Pertanian Negeri Kupang, 2020)
ABSTRACT This study aims to figure out the form of threats to santigi, information on the larceny of santigi and the threat of picking up santigi on its sustainability in Maubesi Nature Reserve. The determination of total interviewe samples uses the technique of snowball sampling. Descriptive analysis is conducted by interviews.The results showed that the form of threats to santigi in Maubesi Nature Reserve was larceny by people from outside the area and exploitation by the local community. The larceny of santigi in Maubesi Nature Reserve was carried out by water using boats and by land using trucks and motorbikes. Sustainability prospect of santigi preservation in Maubesi Nature Reserve is endangered, the larceny and public consumption is not comparable to its slow growth. Key words: Descriptive Analysis, Santigi, Threats of Santigi